HBO Promotes the Differentiation of Neural Stem Cells via Interactions Between the Wnt3/β-Catenin and BMP2 Signaling Pathways. Issue 12 (December 2019) - Chen, Chongfeng; Yang, Yujia; Yao, Yue
Hyperbaric oxygen (HBO) therapy may promote neurological recovery from hypoxic-ischemic encephalopathy (HIE). However, the therapeutic effects of HBO and its associated mechanisms remain unknown. The canonical Wnt/β-catenin signaling pathways and bone morphogenetic protein (BMP) play important roles in mammalian nervous system development. The present study examined whether HBO stimulates the differentiation of neural stem cells (NSCs) and its effect on Wnt3/β-catenin and BMP2 signaling pathways. We showed HBO treatment (2 ATA, 60 min) promoted differentiation of NSCs into neurons and oligodendrocytes in vitro. In addition, rat hypoxic-ischemic brain damage (HIBD) tissue extracts also promoted the differentiation of NSCs into neurons and oligodendrocytes, with the advantage of reducing the number of astrocytes. These effects were most pronounced when these two were combined together. In addition, the expression of Wnt3a, BMP2, and β-catenin nuclear proteins were increased after HBO treatment. However, blockade of Wnt/β-catenin or BMP signaling inhibited NSC differentiation and reduced the expression of Wnt3a, BMP2, and β-catenin nuclear proteins. In conclusion, HBO promotes differentiation of NSCs into neurons and oligodendrocytes and reduced the number of astrocytes in vitro possibly through regulation of Wnt3/β-catenin and BMP2 signaling pathways. HBO may serve as a potential therapeutic strategy for treating HIE.